2016
DOI: 10.1111/ppa.12599
|View full text |Cite
|
Sign up to set email alerts
|

Potato cultivar Etola exhibits hypersensitive resistance to PVYNTN and partial resistance to PVYZ‐NTN and PVYN‐Wi strains and strain‐specific alterations of certain host miRNAs might correlate with symptom severity

Abstract: This study demonstrates the new sources of resistance available in potato cv. Etola, which represent multiple strain-specific resistance genes against three strains of Potato virus Y (PVY). Etola is the first documented cultivar of this sort in Europe that exhibits hypersensitive resistance (HR) to PVY NTN isolate PVY-3202, and different levels of partial resistance to PVY N-Wi isolate PVY-3411 and PVY Z -NTN isolate PVY-3303. The isolate PVY-3411 induced severe symptoms and faster systemic viral coat protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…The abundance of the majority of tested tobacco miRNAs and targets was increased upon infection by PVY NTN and PVY N-Wi isolates, which induced severe symptoms (Yin et al 2019). Our findings indicated that the tested potato and tobacco miRNAs and their targets responded to PVY challenge (Yin et al 2017(Yin et al , 2019; and the alteration patterns of these PVYresponsive miRNAs were host-and strain-dependent and may relate to symptom severity in PVY-host interaction.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The abundance of the majority of tested tobacco miRNAs and targets was increased upon infection by PVY NTN and PVY N-Wi isolates, which induced severe symptoms (Yin et al 2019). Our findings indicated that the tested potato and tobacco miRNAs and their targets responded to PVY challenge (Yin et al 2017(Yin et al , 2019; and the alteration patterns of these PVYresponsive miRNAs were host-and strain-dependent and may relate to symptom severity in PVY-host interaction.…”
Section: Introductionmentioning
confidence: 65%
“…In another study from our group, a temperature-independent but strain type-dependent HR was demonstrated in potato cv. Etola, whereas HR resistance to PVY NTN isolate PVY-3202 and necrotic reaction to PVY Z -NTN isolate PVY-3303 and PVY N-Wi isolate PVY-3411 were observed at temperatures ranging from 20 to 28°C (Yin et al 2017). Recently, in a preliminary study from our group, we found a different type of temperature-dependent potato-PVY interaction in a diploid potato clone DG 81-68.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…PVY N-Wi and PVY NTN belong to the PVY N strain group, and PVY NTN elicits PTNRD in sensitive potato cultivars. In addition, potato cultivars Etola and Gwiazda are used as the indicator for HR (Yin et al, 2017).…”
Section: Identification Of Potato Viruses In the Indicator Plants -A mentioning
confidence: 99%
“…The source for the available primers from the published data is summarized in Table 4. In addition, a method for PVY and TRV wholegenome sequencing and real-time quantitative RT-PCR (real-time RT-qPCR) detection of PVY HC-Pro RNA are referred to in Yin et al (2014Yin et al ( , 2017, and the primer sequences are listed in Table 5. The primer sequences used for detecting of TRV and PMTV by RT-PCR are shown in Table 6.…”
Section: Molecular Assay -Rt-pcr (Reverse Transcription Polymerase Chmentioning
confidence: 99%